The Politics of Foetal Personhood in Argentina: Conservative Catholic Activism, Religion and Gender - Irrazábal, Gabriela (Religion & gender, 2025)
This article explores the intersection of Catholic conservative religious activism, foetal personhood legislation, and women’s lived experiences of miscarriage in Argentina. It shows how these conservative religious groups instrumentalise the concept of foetal personhood within legislative debates, shaping public policy and directly affecting women’s rights and health. To capture the interplay between macro-level politics and personal experiences, I employ a three-pronged analytical approach, including 1) an example illustrative case of collision between conservative legislative pushes and lived experiences, 2) surveys of women who experienced miscarriage, highlighting a needed woman-centred approach often overlooked in legislative and clinical settings and 3) legislative bill strategies to institutionalise foetal personhood. The article explains how Catholic religious conservatism influences reproductive autonomy and public health in Argentina. This study provides an understanding of the socio-political debate on religion, gender, and reproductive rights in Argentina, demonstrating the impact of religious conservatism on reproductive autonomy and public health.